2022
DOI: 10.1021/acsomega.2c00269
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan-Functionalized Mesoporous Silica Nanoparticles for Smart Control of Fungicide Release and Translocation in Plants

Abstract: In this work, an enzyme-responsive nanovehicle for improving captan (CAP) contact fungicide bioactivity and translocation in plant tissues was synthesized (CAP-MSNs-β-glucan) by attaching β-glucan to the outer surface of mesoporous silica nanoparticles. CAP-MSNs-β-glucan properties were tested by FTIR, ζ-potential, DLS, XRD, TGA, FE-SEM, and HR-TEM. Cargo protection ability of CAP-MSNs-β-glucan from photolysis and hydrolysis was examined in comparison to CAP commercial formulation (CAP-CF). CAP-MSNs-β-glucan d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Thus, many designed release systems could only function in the early days of implantation. In the present study, we also used MSNs as the drug carrier for the reason that they possess large surface areas and high pore volumes, resulting in a prolonged drug-release time. , The N 2 adsorption isotherms indicate that MSNs used in this study had a well-defined mesoporous structure with a surface area of 511 m 2 /g and the pore diameter in the range of 3–5 nm (Figure S2). We utilized the soaking method to load CCN2 into MSNs with a drug loading of 1 ng of CCN2 per 3 mg of MSNs.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, many designed release systems could only function in the early days of implantation. In the present study, we also used MSNs as the drug carrier for the reason that they possess large surface areas and high pore volumes, resulting in a prolonged drug-release time. , The N 2 adsorption isotherms indicate that MSNs used in this study had a well-defined mesoporous structure with a surface area of 511 m 2 /g and the pore diameter in the range of 3–5 nm (Figure S2). We utilized the soaking method to load CCN2 into MSNs with a drug loading of 1 ng of CCN2 per 3 mg of MSNs.…”
Section: Resultsmentioning
confidence: 94%
“…The efficiency of pesticide absorption and upward transmission from the roots is related not only to the pesticide properties, but also the plant type, plant growth period, application method and pesticide dosage form. Some studies have shown that methods such as nanoencapsulation technology and the coupling of pesticides with certain molecules can increase the mobility of pesticides in the soil and improve their effective utilization and systemic conductivity 41–43 . In one study, mixed applications of plant growth‐promoting rhizobacteria were used to expand the specific surface area of the plant root system and increase the contact between the pesticide and the root system, thus facilitating the uptake of the pesticide uptake and delivery 44 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PDA coating improved the adhesion ability and deposition efficiency of crop leaves . However, the current research in this field mainly focuses on the release of drug-carrying system on the crop leaf surface, while a similar release in soil is less studied . It is worth mentioning that soil application is also the main means of disease and pest control, especially bacteriostatic ones in wheat early stage.…”
Section: Introductionmentioning
confidence: 99%
“…36 However, the current research in this field mainly focuses on the release of drug-carrying system on the crop leaf surface, while a similar release in soil is less studied. 37 It is worth mentioning that soil application is also the main means of disease and pest control, especially bacteriostatic ones in wheat early stage. Accordingly, it is of great significance to study the slow-release behavior of mesoporous silica-based pesticide delivery system in soil for increasing the wheat yield.…”
Section: Introductionmentioning
confidence: 99%